Rekonstruksi Fiqh dalam Merespon Perubahan Sosial - Harisudin, M. Noor (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2016)
Change  is  sina  qua  none  in  life.  Fiqh  respond  to  changes with the tools that have been prepared. Rigid nature onthe one hand and bending on the other side of the fiqh made itelastic in the face of various  changes.  No  wonder  if  the  views  of  fiqh  changing  following the  change  of  date  and  place  (salihun  likulli  zaman  wa  makan). Precisely there, fiqh finds himself as the legal formulationthat always compitable with all space and time.